Papillary Muscle Hydatid of Heart: A Rare Case of Disseminated Hydatidosis in A Young Female with Multisystemic Involvement - MD, Uma Debi; MD, Lokesh Singh; MD, Muniraju Maralakunte; R, Karthik; MD,; DNB,; FRCR,; MD, Manphool Singhal (Archives of Clinical and Medical Case Reports, 2020)
Hydatid disease, a zoonosis, most commonly caused by the parasite Echinococcus granulosus, involving the cardiac and brain is rare accounting for 0.5-2% and 2-5% respectively. The disseminated hydatid disease is associated with poor prognosis. A 35-year-old, female, from rural background presented cardiac OPD, PGIMER, Chandigarh in 2016 for vague discomfort in the chest and right hypochondrium. Her past medical records revealed neurosurgical intervention for the right frontal cerebral cystic lesion with negative hydatid serology, which was proven to be hydatid cyst on histopathological examination in the year 2011. Increase in the intensity of the above-mentioned chest discomfort. Echocardiography was advised which revealed a cystic lesion in the left ventricle, subsequent cardiac MR examination revealed cystic lesion in anterolateral papillary muscle of the left ventricle and the contrast examination of the abdomen revealed disseminated hydatid disease in abdomen with raised hydatid serology titers at present. Patient requested medical management over surgical intervention, and she was on tablet Albendazole 400mg every 12 Hrs. After 3-4months patient succumbed due to the anaphylaxis resulted from ruptured mesenteric hydatid cyst. Presence of isolated cerebral or cardiac hydatid disease should warrant the physicians to evaluate systematically and follow up the patient frequently with the available cross sectional imaging, which may aid in early detection and holistic management of the patient. Irregular follow up visits or non-intentional negligence of the meticulous evaluation of the subjects with hydatid disease in organs other than liver and lungs, can predispose to the disseminated disease and early mortality as witnessed in the present case.